Вы находитесь на странице: 1из 3

Uso de la Transformada de Laplace

X = AX, X(0) = I (7)

Si x(s) = L{X(t)} = L{eAt}, luego

sx(s) X(0) = Ax(s) or (sI A)x(s) = I

Ahora x(s) = (sI A)1I = (sI A)1. As

L{eAt} = (sI A)1 (8)


Ejemplo 1
Use la Transformada de Laplace para calcular eAt,
donde 1 1
A
2 2
Solucin
s 1 1
sI A
2 s 2
s2 1

1
1 s 1 1 s ( s 1) s ( s 1)
( sI A)
2 s 2 2 s 1
s ( s 1) s ( s 1)

Ejemplo 1 (2)
2 1 1

1

( sI A) s s 1
1 s s 1 (9)
2 2 1 2

s s 1 s s 1

2 e t 1 e t
e At t

t
2 2e 1 2e